Analisis Keterampilan Teknik Dasar Bolavoli: Studi Empiris pada Siswa Peserta Ekstrakurikuler Bolavoli di SMA Negeri 1 Ceper - Zulva Bayu Indra; Vera Septi Sistiasih; Gatot Jariono (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to determine the level of basic volleyball skills of students participating in extracurricular activities at SMA Negeri 1 Ceper using a descriptive quantitative approach with a survey method. The research subjects consisted of 20 male students who actively participated in extracurricular activities and were determined using purposive sampling. Data collection was carried out using a basic volleyball skills test. The data were analysed descriptively by calculating the mean and standard deviation, then classified into five assessment categories. The results showed that the mean scores for underhand passing (87.70), overhand passing (87.35), overhand serve (21.55), and smash (18.80) were in the moderate category. These findings indicate that the students' mastery of basic techniques is not yet optimal and requires reinforcement through a systematically designed and continuous training programme, as emphasised in previous studies on the importance of technical training in volleyball extracurricular activities.